Biotechnological advances in food supplement development from cultivated cereals for sustainable agriculture - Askarov Ibrohimjon; Khasanova Dilorom (E3S Web of Conferences)
The study of the chemical composition of locally cultivated cereal grains in Uzbekistan holds significant practical value, as these crops are rich in essential nutrients due to their adaptation to specific climatic conditions. The potential for utilizing cereal grains as raw materials for complex processing in the food industry, aimed at producing final consumer products and food supplements, is determined by their rich chemical composition and high biological value. In particular, methods for selecting optimal conditions for processing cereal grains and developing food supplements, along with the analysis of their chemical composition, play a crucial role in the production of various functional food products. This research employs modern biotechnological approaches and advanced analytical techniques for the techno-chemical analysis of cereal grains. The integration of these biotechnological methods not only enhances the nutritional value of the developed food supplements but also contributes to sustainable agricultural practices and food security.